Molecular Epidemiology and Antimicrobial Resistance of Extended-Spectrum β-Lactamase (ESBL)-Producing Klebsiella pneumoniae in Retail Cattle Meat - Nasrin Akter Liza; Hemayet Hossain; Md. Shahidur Rahman Chowdhury; Jarin Al Naser; Rayhan Mahmud Lasker; Asikur Rahman; Md. Ariful Haque; Md. Al Mamun; Md. Mukter Hossain; Md. Mahfujur Rahman (Veterinary Medicine International)
Enterobacteriaceae that produce extended-spectrum β-lactamases (ESBLs) can result in severe human infections, contributing to the development of complex diseases. Klebsiella pneumoniae is one of the ESBL-producing pathogens that helps to set antimicrobial resistance as a major public health problem worldwide. The current study aimed to isolate, identify, and characterize ESBL-producing K. pneumoniae and their antimicrobial resistance pattern in retail cattle meat samples. A comprehensive set of 225 cattle meat samples was gathered from 13 upazilas within the Sylhet district of Bangladesh. The bacterial isolates were obtained through biochemical and cultural techniques, and the identification of K. pneumoniae was accomplished using polymerase chain reactions (PCRs). Antimicrobial susceptibilities were assessed using disk diffusion in accordance with the Clinical and Laboratory Standards Institute (CLSI, 2020) guidelines. Genes encoding ESBL enzymes were detected by the double-disk synergy test (DDST) and multiplex PCR. The overall prevalence of Klebsiella spp. was 28.89% (65/225), whereas the positive percentage of K. pneumoniae was 59.2% (29/49) confirmed by PCR. Antimicrobial resistance was observed against 12 antibiotics. According to the phenotypic resistance pattern determined through the disk diffusion method, all isolates (100%) were resistant to ampicillin, amoxicillin, cefuroxime, cefotaxime, and colistin. On the other hand, the highest susceptibility was observed towards gentamicin (97.95%), followed by ciprofloxacin (85.71%), tetracycline (83.67%), and trimethoprim-sulfamethoxazole (81.63%). Out of the total K. pneumoniae isolates analyzed, ESBL genes were present, and the highest percentage, 82.8% (24/29), tested positive for blaTEM genes. Interestingly, among the nine ESBL genes, six were identified in K. pneumoniae isolates, except for blaOXA, blaCTX‐M‐grp2, and MultiCaseDHA. The study’s results reveal the presence of extended-spectrum β-lactamase (ESBL)-producing multidrug-resistant (MDR) K. pneumoniae in retail cattle meat samples posing a substantial public health threat.